Quantitative characteristics of mesofauna and microarthropoda in main biotops of khu hamlet, Thuong Tien protected area, Hoa Binh province - Bai, Thai Tran; Thanh Binh, Tran Thi; Tien, Nguyen Tri; Bich Ngoc, Nguyen Thi (Academia Journal of Biology, 2014)
The data of Mesofauna are recorded in main biocenoses (forest of wood trees, forest of bamboo, savan of blady grass and garden around home) of Khu hamlet during surveys conducted from December 2004 to August 2005 (table 1 and figs 1, 2). Earthworms is the most abundant in density and biomass more than those of insects. In comparing earthworms with all arthropods, density of arthropods is more than earthworms but their biomass is clearly lower. Collembola is abundant in microarthropods. 63 species of Collembola in 12 families are found in Khu hamlet (tables 2, 3 and figs 3, 4). The table 4 shows that species number, density and biomass of many groups of soil invertebrate are decreased from natural biocenoses (forest of wood trees, forest of bamboo) to anthropogene ones (blady grass and garden around home), while the density and biomass of earthworms and collembola changed in opposite direction, that is explained by the development of some eurytopic species in anthropogene specified biocenoses. Soil invertebrates condensed in litter and in 30 cm upper layer of soil.